Nutrition - Brown, Judith E. (Singapore, 2009)
Nutrition is oriented toward helping students build a foundation of knowledge about nutrition that will serve them well throughout life. Units are concise, focused on key facts and concepts, and provide ample real-life examples intended to enhance students' understanding of the material presented. Students are asked to apply their newly gained knowledge about nutrition in decision-making activities and exercises incorporated throughout the units.
Keywords: Nutrition